Preservation of the Antioxidant Capacity of Resveratrol via Encapsulation in Niosomes - Noelia D. Machado; Gemma Gutiérrez; María Matos; Mariana A. Fernández (Foods, 2021)
Resveratrol (RSV) is a natural polyphenol which produces several benefits to human health, being the trans-isomer the most bioactive. However, its systemic absorption is limited due to its low water solubility, that reduces the oral bioavailability, and its chemical instability (owing to the trans-cis RSV isomer conversion upon light irradiation). Thus, encapsulation of this bioactive compound is required to protect it from destructive environmental conditions. Here, trans-RSV was encapsulated in food grade nanovesicles formed by Tween 80 and Span 80, with or without the addition of dodecanol (Dod) as membrane stabilizer. The size and shape of niosomes were evaluated by microscopy (TEM) and light scattering. RSV was successfully encapsulated in the vesicular systems (49–57%). The effect of Dod in the membrane bilayer was evaluated on the RSV in vitro release experiments under simulated gastrointestinal conditions. The total antioxidant capacity of the encapsulated polyphenol was measured using radicals’ assays (DPPH and ABTS). The niosomes were able to maintain almost the total antioxidant capacity of encapsulated RSV, also preserved the ~85% of trans-RSV, thus offering considerable protection against high energy irradiation. These results make these systems suitable for different applications, particularly for photosensitive compounds.